Predictive value of the risk factors for amputation of lower extremity in patients with diabetic foot in Al-Karama teaching hospital - Surriah, Mohammed Hillu; Al-Imari, Amir Naif Kadum; Bakkour, Amine Mohammed; Al-Asadi, Riad Rahman Jallod (International Surgery Journal, 2019)
Background: Diabetic foot disease is a foot that exhibits any pathology that results directly from diabetic mellitus or any long-term chronic complication of diabetes mellitus. The aim of the study was to determine the risk factors and indications for amputations among diabetics. Methods: this clinical prospective study includes 120 diabetic foot patients admitted to AL- Karama teaching hospital from 1st January 2015 to 1st January 2019. All patients assessed for age, gender, duration of diabetes, hyperglycemia at admission and control of diabetes, history of smoking, hypertension, assess dominant foot and examination of diabetic foot lesion and classify it according to Meggit-Wagner grading status, indications for amputation and outcome. Results: The male to female ratio was 2:1. Most frequent age group of patients treated by amputation was between 50-80 years. Among patients treated with amputation (68.33%) of patients had diabetes mellitus for 11-20 years. From patients admitted with diabetic foot (53.33%) were smokers. Regarding hypertension (93.33%) of all patients were hypertensive. It was noted that (65%) of patients lesion occur in dominant foot Regarding Wagner's grading system (36.66%) of patients were grade 4 followed by grade 1 (21.66%). regarding mode of treatment (53.33%) of patients treated by amputation and other treated conservatively. Only 3 patients from 60 died while other discharged well after complete treatment. Conclusions: Increasing in age, long duration of diabetes mellitus, poor control of diabetes, smoking and occurrence of lesion in dominant foot all considered as a significant risk factors for increase liability amputation.